KAJIAN ADAPTASI BEBERAPA VARIETAS UNGGUL JAGUNG DI KABUPATEN MALUKU BARAT DAYA (MBD) - Sheny Sandra Kaihatu; Florentina Watkaat (Agric, 2015)
Adaptation study of hybrid maize varieties and improved varieties do subdistrict Wonreli Southwest Maluku district from September to December 2012. Study using a randomized block design repeated 3 times and farmers as replicates. Varieties tested is the Bima-3, Bima-4, Bima-5, Srikandi kuning, Lamuru, Lagaligo and Lokal MBD as a comparison. Fertilization is done drill, a distance of 5-7 cm from the plant, fertilizer dose of 300 kg urea, 200 kg SP-36, 100 kg of KCl and 1-2 t.ha-1manure. Urea fertilizer done twice, is 100 kg urea and entire SP36 and KCl at the age of 7-10 plants hst and residual urea 200 kg administered at 30 dap. Parameters observed plant height at harvest, High cob, cob diameter, cob length, number of rows/cob, number of grains / row, weight of 1000 seeds and Yield per hectare. The results of the study showed that of the varieties tested turned out varieties Bima-5 higher result of (6.7 t.ha-1) and the lowest result is Lokas MBD ( 5.7 t.ha-1).